P-165 Cytometry-Based Single Cell Analysis of Intact Epithelial Signaling Reveals MAPK Activation Divergent from TNF-α-Induced Apoptosis in Vivo. (March 2016) - Simmons, Alan; Banerjee, Amrita; McKinley, Eliot; Scurrah, Cherie'; Franklin, Jeffrey; Gerdes, Michael; Irish, Jonathan; Coffey, Robert; Lau, Ken
Abstract : Background: TNF (tumor necrosis factor) is a master proinflammatory cytokine of central importance in both Crohn's Disease and Ulcerative Colitis. A central biochemical property of TNF is its ability to engage in the cell death signaling program to induce cell apoptosis. TNF induces apoptotic cell shedding in the differentiated intestinal epithelium, which can lead to barrier defects allowing inappropriate interaction between luminal microbes and the host. It is not understood why apoptosis occurs intermittently throughout the differentiated compartment and never in patches, even though all cells are equally exposed to TNF. We developed a single cell approach to delineate heterogeneous signaling programs, and used it to understand heterogeneous TNF responses in the intestinal epithelium at single cell resolution. Methods: We evaluated a mouse model of acute TNF stimulation by intravenous injection of TNF to induce intestinal epithelial apoptosis. Understanding heterogeneous cellular behaviors in a complex tissue requires the evaluation of signaling networks at single cell resolution. However, probing signaling in epithelial tissues using cytometry-based single cell analysis has been confounded by the necessity of single cell dissociation, where disrupting cell-to-cell connections inherently perturbs native cell signaling states. Here, we demonstrate a novel strategy (Disaggregation for Intracellular Signaling in Single Epithelial Cells from Tissue—DISSECT) that preserves intact signaling for Cytometry Time-of-Flight (CyTOF) and fluorescent flow cytometry applications. A 21-plex CyTOF analysis encompassing core signaling and cell-identity markers was performed on the small intestinal epithelium after TNF stimulation. Results: Multiplex single cell data consisting of hundreds of thousands of data points was analyzed with unsupervised and supervised quantitative methods to robustly select signaling features that identify a unique subset of epithelial cells that are sensitized to TNF-induced apoptosis in the seemingly homogeneous enterocyte population. Specifically, p-ERK and apoptosis are divergently regulated in neighboring enterocytes within the epithelium, suggesting a mechanism of contact-dependent survival. We propose a model where dying cells signal to their direct epithelial neighbors to activate a survival program, in order to prevent large swaths of neighboring cells from dying. Conclusions: Our novel approach can be broadly applied, using both CyTOF and multi-parameter flow cytometry, for investigating intact signaling networks of a wide range of epithelial tissues in healthy and diseased states. Future integration of single-cell signaling, transcriptomics, and imaging provide exciting opportunities for comprehensively understanding in vivo gastrointestinal biology.